Long-term outcomes after treatment of bare-metal stent restenosis with paclitaxel-coated balloon catheters or everolimus-eluting stents: 3-year follow-up of the TIS clinical study - Pleva, Leos; Kukla, Pavel; Zapletalova, Jana; Hlinomaz, Ota (Catheterization and cardiovascular interventions, 2018)
BACKGROUND: The efficacy of paclitaxel-eluting balloon catheters (PEB) and drug-eluting stents for treatment of bare-metal stent restenosis (BMS-ISR) have been demonstrated in several studies with follow-up times of 9 to 12 months; however, the long-term outcomes of ISR treatment are less defined. OBJECTIVES: We aimed to compare the long-term efficacy of PEB and everolimus-eluting stents (EES) for the treatment of BMS-ISR. METHODS: We analyzed 3-year clinical follow-up data from patients included in the TIS randomized clinical study. A total of 136 patients with BMS-ISR were allocated to receive treatment with either PEB or EES (68 patients with 74 ISR lesions per group). RESULTS: The PEB and EES groups did not significantly differ in major adverse cardiac events-free survival (MACE; P = .211; including individual events: CV death: P = .622; myocardial infarction: P = .650 or target vessel revascularization: P = .286) at 3-year clinical follow-up. No event-free survival differences were found between the groups regarding overall mortality (P = .818), definite stent thrombosis (P = .165) or the second MACE (P = .270). CONCLUSIONS: At the 3-year follow-up, no significant differences in clinical outcomes were found between iopromide-coated PEB and EES for the treatment of BMS-ISR. (ClinicalTrials.gov; https://clinicaltrials.gov; NCT01735825).
Keywords: srdeční katétry; Coated Materials, Biocompatible; Female; Prosthesis Design; Everolimus; balónková koronární angioplastika; protézy - design; ženské pohlaví; doba přežití bez progrese choroby; Metals; kardiovaskulární látky; koronární restenóza; Retreatment; časové faktory; biokompatibilní potahované materiály; stenty uvolňující léky; Time Factors; lidé; Coronary Restenosis; Drug-Eluting Stents; everolimus-eluting stent; koronární angioplastika; everolimus; kovy; Paclitaxel; Risk Factors; Percutaneous Coronary Intervention; prospektivní studie; Male; Aged; Cardiovascular Agents; Prospective Studies; opakovaná terapie; Stents; in-stent restenosis; paclitaxel; Angioplasty, Balloon, Coronary; rizikové faktory; lidé středního věku; senioři; mužské pohlaví; Cardiac Catheters; Progression-Free Survival; Middle Aged; stenty; paclitaxel-eluting balloon; Humans